Developing evaluation tools for assessing the educational potential of apps for preschool children in the UK. Issue 3 (3rd July 2021) - Kolak, Joanna; Norgate, Sarah. H.; Monaghan, Padraic; Taylor, Gemma
ABSTRACT: Selecting high-quality apps can be challenging for caregivers and educators. We here develop tools evaluating educational potential of apps for preschool children. In Study 1, we developed two complementary evaluation tools tailored to different audiences. We grounded them in developmental theory and linked them to research on children's experience with digital media. In Study 2 we applied these tools to a wide sample of apps in order to illustrate their use and to address the role of cost in quality of educational apps. There are concerns that a social disadvantage may lead to a digital disadvantage, an "app gap". We thus applied our tools to the most popular free (N = 19) and paid (N = 24) apps targeting preschoolers. We found that the "app gap" associated with cost is only related to some aesthetic features of apps rather than any observable educational advantage proffered by paid apps. Our study adds a novel contribution to the research on children's apps by developing tools to be used across a wide range of audiences, providing the first description of the quantity of app design features during app use and evaluating the educational potential of free and paid apps.